(untitled) (Annals of Medical Research, 2021)
Aim: Long term control of glucotoxicity was shown to increase the secretion of insulin and C-peptide (Cp). We aimed to investigate the change in Cp levels after short term glycemic control in patients with uncontrolled type 2 diabetes mellitus (DM).Material and Methods: Patients with type 2 DM with uncontrolled hyperglycemia were included. Basal fasting Cp levels were measured both at admission (Cp-admission) and after control of hyperglycemia prior to discharge (Cp-discharge). Cp-difference was calculated as (Cp-discharge)-(Cp-admission). The patients were divided as group 1 (positive Cp-difference) and group 2 (negative Cp-difference), and group A (Cp-difference ≥+0.5) and group B (Cp-difference ≤-0.5).Results: Of the patients (n=123), 61.8% had positive Cp-difference, and mean Cp-differences were 0.16 (±1.59), 0.96 (±1.03), and -1.11 (±1.51) in all patients, group1 and 2; respectively (p=0.001). Mean body weight, creatinine and Cp-discharge were higher in group 1(p=0.045, p=0.013, p=0.001; respectively). Mean age, body mass index(BMI), diabetes duration, hospitalization, proteinuria, fasting and postprandial glucose, glucose-discharge, HbA1c, lipids, TSH, free T4, Cp-admission were similar in group 1 and 2.Cp-difference was correlated positively with Cp-discharge(p=0.001), negatively with Cp-admission (p=0.001). There were no significant differences between subgroups (age, BMI, diabetes duration, use of secretagogue, diabetic ketaoacidosis history, HbA1c (10 or ≥10%), hyperlipidemia, microvascular complication) regarding to Cp-difference. Positive predictors of positive Cp-difference were cardiovascular disease (p=0.004; Odds Ratio(OR)=3.006) and higher Cp-discharge(p=0.001; OR=6.420);positive predictors of Cp-difference ≥+0.5 were male, lower Cp-admission and higher Cp-discharge.Conclusion: Our results indicate that short-term glycemic control has little but significant positive effect on basal Cp. Having cardiovascular disease was positive predictor for positive Cp-difference.